latihan Keterampilan Mental bagi Siswa Atlet SMAN 9 Gowa untuk Mendukung Performa Optimal - Hamid, Muflih; Musfira, Nurul; Mahyuddin, Reza; Shadzali, Muhammad; Rhesa, Muhammad (Yayasan Sinergi Widya Nusantara, 2025)
Mental skills training is a vital component in enhancing athletes' performance, particularly for students actively participating in sports competitions. SMAN 9 Gowa, a school renowned for consistently competing and winning in various championships, had not previously received training in sports psychology. This program aimed to: (1) introduce the fundamentals of sports psychology and its benefits for athletic performance, and (2) teach practical techniques such as goal setting, mental imagery, self-talk, and energization and relaxation strategies. The training was conducted over one day, combining theoretical and practical approaches, and involved 15 student-athletes from diverse sports disciplines. Evaluation was carried out through pre-test and post-test assessments to measure participants' knowledge improvement. The results revealed a significant increase in students' understanding of sports psychology techniques. This program made a positive contribution to the mental preparedness of students in facing sports competitions. It is recommended that similar training programs be implemented in other schools to further support young athletes' mental development.